Temporal and spatial dynamics of immune cells in spontaneous liver transplant tolerance - Weitao Que; Hisashi Ueta; Xin Hu; Miwa Morita-Nakagawa; Masayuki Fujino; Daisuke Ueda; Nobuko Tokuda; Wenxin Huang; Wen-Zhi Guo; Lin Zhong; Xiao-Kang Li (iScience, 2023)
Summary: The liver has long been deemed a tolerogenic organ. We employed high-dimensional mass cytometry and immunohistochemistry to depict the temporal and spatial dynamics of immune cells in the spleen and liver in a murine model of spontaneous liver allograft acceptance. We depicted the immune landscape of spontaneous liver tolerance throughout the rejection and acceptance stages after liver transplantation and highlighted several points of importance. Of note, the CD4+/CD8+ T cell ratio remained low, even in the tolerance phase. Furthermore, a PhenoGraph clustering analysis revealed that exhausted CD8+ T cells were the most dominant metacluster in graft-infiltrating lymphocytes (GILs), which highly expressed the costimulatory molecule CD86. The temporal and spatial dynamics of immune cells revealed by high-dimensional analyses enable a fine-grained analysis of GIL subsets, contribute to new insights for the discovery of immunological mechanisms of liver tolerance, and provide potential ways to achieve clinical operational tolerance after liver transplantation.